2016
DOI: 10.18632/oncotarget.13037
|View full text |Cite
|
Sign up to set email alerts
|

miR-22 targets YWHAZ to inhibit metastasis of hepatocellular carcinoma and its down-regulation predicts a poor survival

Abstract: ABSTRACT

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
34
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 41 publications
(37 citation statements)
references
References 55 publications
3
34
0
Order By: Relevance
“…Interestingly, Chen et al 21 suggested urinary protein of YWHAZ expression was decreased in NSCLC cancer patients. 27 In our study, we assessed the prognostic value of YWHAZ in NSCLC patients through analyzing the TCGA database, and found YWHAZ expression was negatively correlated with overall survival time in lung adenocarcinoma patients, but not significantly associated overall survival time in lung squamous cell carcinoma patients. In our study, we further evaluate the clinical significance of YWHAZ in NSCLC cases through analyzing the associations between clinicopathological characteristics and YWHAZ protein expression, and found YWHAZ overexpression was correlated with advanced clinical stage, more lymph node metastasis and present distant metastasis.…”
Section: Discussionmentioning
confidence: 97%
“…Interestingly, Chen et al 21 suggested urinary protein of YWHAZ expression was decreased in NSCLC cancer patients. 27 In our study, we assessed the prognostic value of YWHAZ in NSCLC patients through analyzing the TCGA database, and found YWHAZ expression was negatively correlated with overall survival time in lung adenocarcinoma patients, but not significantly associated overall survival time in lung squamous cell carcinoma patients. In our study, we further evaluate the clinical significance of YWHAZ in NSCLC cases through analyzing the associations between clinicopathological characteristics and YWHAZ protein expression, and found YWHAZ overexpression was correlated with advanced clinical stage, more lymph node metastasis and present distant metastasis.…”
Section: Discussionmentioning
confidence: 97%
“…In a previous study, Chen et al evidenced that YWHAZ was a favorable target of miR-22 for inhibiting metastasis of hepatic cancer. The study by Chen et al also suggested that miR-22 inhibited YWHAZ mediated phosphorylation of AKT in hepatic carcinoma cells [24]. However, it has been found that YWHAZ is responsible for activating AKT signaling, which in turn elevates the protein stability of CBFA1 by decreasing SMURF2 mediated degradation of CBFA1 [15].…”
Section: Discussionmentioning
confidence: 98%
“…Similarly, YWHAZ mRNA expression was higher in eight liver cancer cell lines than normal liver cell line [5]. Zhao JF et al and Chen M et al likewise verified the high mRNA level of YWHAZ in 50 HCC tissues and 374 HCC tissues respectively from The Cancer Genome Atlas (TCGA) database [5,10]. Additionally, YWHAZ protein expression was also higher in 11 of 12 HCC tissues and 8 liver cancer cell lines by western blot and was enhanced in 72 of 135 HCC tissues by immunohistochemical (IHC) [5,11].…”
Section: Hepatocellular Carcinomamentioning
confidence: 85%
“…FoxO3 had been verified as a key protein in the suppression of cancer progression, with roles including control of differentiation and tumorigenicity through the PI3K/Akt/mTOR and MEK/ ERK signaling pathways [55][56][57]. Nuclear accumulation of FOXO3a could be promoted by miR-22 and was observed to subsequently reverse invasive phenotype of HCC cells through repression of YWHAZ-mediated AKT phosphorylation [10]. Besides, the expression of YWHAZ could be negatively regulated by miR-30c in cervical cancer, by miR-544 in breast cancer, and by miR-613 in HCC [58][59][60].…”
Section: Upstream Regulators Of Ywhazmentioning
confidence: 99%
See 1 more Smart Citation